Hydroxychloroquine is associated with lower seroconversion upon 17DD-Yellow fever primovaccination in patients with primary Sjögren’s syndrome - Ketty Lysie Libardi Lira Machado; Ismael Artur da Costa-Rocha; Laura Gonçalves Rodrigues Aguiar; Isac Ribeiro Moulaz; Samira Tatiyama Miyamoto; Priscila Costa Martins; Erica Vieira Serrano; Ana Paula Espíndula Gianordoli; Maria da Penha Gomes Gouvea; Maria de Fatima Bissoli; Sheila Maria Barbosa de Lima; Waleska Dias Schwarcz; et al. (Human Vaccines & Immunotherapeutics)
The present study aimed at investigating whether the hydroxychloroquine (HCQ) treatment would impact the neutralizing antibody production, viremia levels and the kinetics of serum soluble mediators upon planned 17DD-Yellow Fever (YF) primovaccination (Bio-Manguinhos-FIOCRUZ) of primary Sjögren’s syndrome (pSS). A total of 34 pSS patients and 23 healthy controls (HC) were enrolled. The pSS group was further categorized according to the use of HCQ (HCQ and Non-HCQ). The YF-plaque reduction neutralization test (PRNT ≥1:50), YF viremia (RNAnemia) and serum biomarkers analyses were performed at baseline and subsequent time-points (Day0/Day3–4/Day5–6/Day7/Day14-D28). The pSS group showed PRNT titers and seropositivity rates similar to those observed for HC (GeoMean = 238 vs 440, p = .11; 82% vs 96%, p = .13). However, the HCQ subgroup exhibited lower seroconversion rates as compared to HC (GeoMean = 161 vs 440, p = .04; 69% vs 96%, p = .02) and Non-HQC (GeoMean = 161 vs 337, p = .582; 69% vs 94%, p = .049). No differences in YF viremia were observed amongst subgroups. Serum biomarkers analyses demonstrated that HCQ subgroup exhibited increased levels of CCL2, CXL10, IL-6, IFN-γ, IL1-Ra, IL-9, IL-10, and IL-2 at baseline and displayed a consistent increase of several biomarkers along the kinetics timeline up to D14–28. These results indicated that HCQ subgroup exhibited a deficiency in assembling YF-specific immune response elicited by 17DD-YF primovaccination as compared to Non-HCQ subgroup. Our findings suggested that hydroxychloroquine is associated with a decrease in the humoral immune response after 17DD-YF primovaccination.